Blood monocyte subtypes in patients with pulmonary tuberculosis infection - Tamer G El-Rab Attia; Mona M Abdelmeguid; Ali S Mohammed; Hamada K.S Fayed (Wolters Kluwer Medknow Publications, 2022)
Background and aim Monocytes are the primary target for Mycobacterium tuberculosis infection. Important alterations in the proportions of circulating monocyte subpopulations were found in patients with active tuberculosis (aTB). Our aim was to investigate the peripheral blood monocyte subsets in patients with active pulmonary tuberculosis (aPTB) and to evaluate their role in treatment response. Patients and methods A case-control study included 30 patients with aPTB and 30 healthy controls. Laboratory investigations include sputum examination, tuberculin test, and nucleic acid amplification test using GeneXpert MTB/RIF assay on sputum sample for patients only to confirm the diagnosis of aPTB. For all participants; complete blood count, erythrocyte-sedimentation rate, HIV antibodies, and flow cytometry analysis of peripheral blood monocyte subsets were done using surface markers CD14 phycoerythrin cyanin 7 and CD16 fluoroisothiocyanate for identification of monocyte subsets. Flow cytometry analysis was repeated 2 months after the start of treatment in aTB patients only. Results Classical monocytes were decreased while intermediate, and nonclassical monocytes were increased in aTB patients before treatment more than after 2 months of treatment and control group (P≤0.0001 for each). There was no significant difference in the three monocyte subsets between PTB patients after treatment and healthy controls. Also, the classical monocytes decreased while intermediate, and nonclassical monocytes increased in aTB patients with positive tuberculin test more than healthy controls with positive tuberculin test (P<0.0001 for each). Conclusion The expansion of CD16+ monocytes was reversed after treatment with anti-TB drugs and could be used to follow up tuberculous patients for treatment effectiveness.